Psychological Skills Characteristics of Athletics, Weightlifting, Cycling, Swimming, and Waterskiing Athletes based on the Medal Achievements in the 2017 SEA Games - Ipa Sari Kardi (Universitas Pendidikan Indonesia, 2019)
The purpose of this study was to describe the mental skill characteristics of athletics, weightlifting, cycling, swimming, and waterskiing athletes based on medal achievements in the 2017 SEA Games. The study was a quantitative research with an ex-post facto method with retrospective causal-comparative design. The sample of the study were 36 athletes from five sports who gained gold, silver, and bronze medals. The variables of this study were psychological characteristics including the aspects of motivation, confidence, anxiety control, mental preparation, team emphasis, and concentration. Data collection used The Psychological Skills Inventory for Sports as the instrument. The results of the study show that athletes in athletic sports, who received three gold medals, had higher psychological skill characteristics than other sports. Meanwhile, athletes in cycling sports had lower mental skills than other sports, with a maximum gain of two silver medals. AbstrakTujuan penelitian ini untuk menggambarkan karakteristik keterampilan psikologis atlet cabang olahraga atletik, angkat besi, balap sepeda, renang dan ski air ditinjau dari prestasi di SEA Games 2017 berdasarkan perolehan medali. Menggunakan jenis penelitian kuantitatif dengan metode ex post facto dengan desian penelitian yaitu a restrospective causal-comparative design. Sampel penelitian berjumlah 36 atlet dari lima cabang olahraga yang memperoleh medali baik emas, perak dan perunggu. Variabel dalam penelitian ini yaitu karakteristik psikologis yang meliputi, aspek motivasi, percaya diri, kontrol kecemasan, persiapan mental, pentingnya tim, dan konsentrasi. Pengumpulan data menggunakan instrumen The Psychological Skills Inventory for Sports. Hasil penelitian menunjukkan bahwa atlet cabang olahraga atletik memiliki karakteristik keterampilan psikologis lebih tinggi dari cabang olahraga lainnya dengan perolehan tiga medali emas. Sedangkan atlet cabang olahraga balap sepeda memiliki karakteristik keterampilan psikologis lebih rendah dari cabang olahraga lainnya dengan maksimal memperoleh dua medali perak.